Pengembangan Media Pembelajaran Dengan Menggunakan Aplikasi Canva Pada Pembelajaran Bahasa Arab Untuk Meningkatkan Hasil Belajar Siswa Kelas IXB Di Mts Al-Azhar Samarinda - Abusyairi, Khairy; Zulkifli, Edy Murdani; Mulyani, Rinda Eka (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2021)
The This research is motivated by the lack of innovation in the use of learning media at MTs Al-Azhar Samarinda, so it is necessary to develop learning media to create an active and interesting learning atmosphere. The type of this research is research and development (research and development/R&D). The development model used in this study is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Research and development is a process or method used to validate and develop products. The product developed in this study is an audiovisual video learning media with the help of the Canva application for learning Arabic. The results showed that there was a difference between the control class and the experimental class. This could be seen from the results of the N-gain test in the control class which was included in the ineffective category, while the experimental class was included in the quite effective category. Based on the results of the paired T test, it states that the use of learning media that has been developed using Canva has a significant difference between the experimental class and the control class. Based on these results, it can be seen that the development of learning media using the Canva application has an effect on learning Arabic for class IXB students at MTs Al-Azhar Samarinda.